2013
DOI: 10.1016/j.ijrobp.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of 4-Dimensional Computed Tomography-Based Ventilation Imaging to Correlate Lung Dose and Function With Clinical Outcomes

Abstract: Purpose Four-dimensional computed tomography (4DCT)-based ventilation is an emerging imaging modality that can be used in the thoracic treatment planning process. The clinical benefit of using ventilation images in radiation treatment plans remains to be tested. The purpose of the current work was to test the potential benefit of using ventilation in treatment planning by evaluating whether dose to highly ventilated regions of the lung resulted in increased incidence of clinical toxicity. Methods and Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 19 publications
1
104
0
Order By: Relevance
“…For the lungs, the following dose-volume metrics were investigated: the mean lung dose (MLD), V 20 , and effective dose (D eff ) [28]. We also calculated the dose-function histogram (DFH) [29] and the following dose-function metrics: fV 20 , functional MLD (fMLD) [30], and functional effective dose (fD eff ) [7]. Vinogradskiy et al demonstrated a higher predictive power of these dose-function metrics for pneumonitis compared to dose-volume metrics [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the lungs, the following dose-volume metrics were investigated: the mean lung dose (MLD), V 20 , and effective dose (D eff ) [28]. We also calculated the dose-function histogram (DFH) [29] and the following dose-function metrics: fV 20 , functional MLD (fMLD) [30], and functional effective dose (fD eff ) [7]. Vinogradskiy et al demonstrated a higher predictive power of these dose-function metrics for pneumonitis compared to dose-volume metrics [7].…”
Section: Discussionmentioning
confidence: 99%
“…The CT ventilation images were smoothed using a 3D Gaussian filter kernel (7 Â 7 Â 3 or 9 Â 9 Â 3 depending on the CT voxel dimension) to match the expected spatial resolution of the SPECT ventilation images. Then, the smoothed CT ventilation images and original (unsmoothed) SPECT ventilation images were converted into percentile distribution images by replacing the ventilation value of each voxel with the corresponding cumulative distribution function (CDF k ) scaled to the range [0,1] (mean 0.5) in a manner similar to Vinogradskiy et al [7]. Abbreviations: SCLC = small-cell lung cancer, NSCLC = non-small-cell lung cancer, RUL = right upper lobe.…”
Section: Imrt Optimization For Functional Image-based Treatment Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…4DCT‐ventilation has been gaining momentum in radiation oncology because 4DCT simulations are frequently acquired as part of the standard treatment planning process; which enables the calculation of 4DCT‐ventilation‐based lung function without burdening the patient with an extra imaging procedure. There have been two clinical applications of 4DCT‐ventilation in radiation oncology: functional radiotherapy (designing radiation treatment plans that minimize dose to functional lung) and thoracic treatment assessment 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%